Verbandsautonomie im Sport Bestimmung der rechtlichen Grenzen unter besonderer Berücksichtigung des europäischen Kartellrechts - Heermann, Peter W. (Neue Schriften zum Zivilrecht, 2022)
Sports associations regularly enact or amend the associations' statutes and, in doing so, establish regulations which can have a restrictive effect on association members, furthermore on third parties. Through this, sports associations usually invoke the association's autonomy, which, however, is subject to (anti-trust) legal limits. The author examines this highly controversial area of law with special reference to the so-called Meca-Medina test, and then applies his approach to numerous practical and highly topical examples. This first comprehensive presentation of sports antitrust law is aimed at sports lawyers, sports associations, those (in)directly affected by sports associations' regulations, courts, but also at legal scholars as well as students.